Hubungan Tingkat Pengetahuan Mahasiswi Tentang Bahan Paraben Dengan Sikap Memilih Kosmetika Perawatan - Fuad, Iqlima; Maspiyah, Maspiyah; Pritasari, Octaverina; Wijaya, Nieke (Universitas Negeri Surabaya, 2025)
Care cosmetics must contain preservatives in their formulation with the aim of protecting the product and the user. However, there is a misunderstanding towards cosmetic preservatives which is paraben. The purpose of this study is to 1) determine the level of knowledge of female students about paraben in cosmetics; 2) determine the attitudes of choosing skincare cosmetics; 3) determine the relation between the level of knowledge and attitudes. The research method used is a correlation study with a quantitative approach. The population in this study is female students of Cosmetology Education at Unesa and the sample in this study is 103 female students of Cosmetology Education at Unesa who have taken the cosmetology course. This study uses Purposive Sampling technique. The research procedure includes preparing research instruments such as questions and questionnaires, distributing questions and questionnaires to respondents, and evaluating answers from respondents. The data analysis technique used is the chi-square test to measure the relation between knowledge and attitudes. The results of the study show that 78.28% of respondents have high knowledge, then 66.95% of respondents have good attitudes of choosing cosmetics, and the Asymptotic significance value (2-sided) is 0.0001 which is below 0.5, indicating that knowledge has a significant relations with attitudes. Thus, the high level of knowledge of Cosmetology Education students about paraben substances is related to the good attitudes of choosing skincare cosmetics.Keywords: Knowledge, Attitudes Of Choosing, Paraben, Relations